2019
DOI: 10.1103/physrevfluids.4.074309
|View full text |Cite
|
Sign up to set email alerts
|

Experimental estimation of turbulence modification by inertial particles at moderateReλ

Abstract: We advance a novel method to estimate the carrier-flow dissipation εp in the presence of inertial sub-kolmogorov particles at moderate Re λ . Its foundations rely on the unladen flow dissipation calculation using the Rice theorem, and the density of zero crossings of the longitudinal velocity fluctuation u (x) coming from a LDA device. Our experimental results provide strong evidence, for the first time, regarding the non-negligible effect that sub-kolmogorov particles have on the carrier flow energy cascade a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Tables 1 Bose et al [38], Monchaux and Dejoan [39] and Malloupas et al [40] showed that two-way coupling makes some difference to the results even for α in the range of 10 -5 to 10 -4 if Reλ < 50, where Reλ is the Reynolds number based on the Taylor microscale length. However, Mora et al [41] found that two-way coupling has some effect on dissipation and settling time for the fluid droplets in their study with Reλ up to 400 or 500. For the flow conditions in the current study, Reλ is in the range 3000 -18000.…”
Section: Cfd Model Description and Simulation Detailsmentioning
confidence: 82%
“…Tables 1 Bose et al [38], Monchaux and Dejoan [39] and Malloupas et al [40] showed that two-way coupling makes some difference to the results even for α in the range of 10 -5 to 10 -4 if Reλ < 50, where Reλ is the Reynolds number based on the Taylor microscale length. However, Mora et al [41] found that two-way coupling has some effect on dissipation and settling time for the fluid droplets in their study with Reλ up to 400 or 500. For the flow conditions in the current study, Reλ is in the range 3000 -18000.…”
Section: Cfd Model Description and Simulation Detailsmentioning
confidence: 82%
“…The tensor invariants of Reynolds stress imply the geometrical and physical information of turbulence fluctuations, which are denoted as Ig,x, Ig,y and Ig,z. using the components of normal and shear Reynolds stress, see Equations ( 7), ( 8) and (9). Now that invariants indicate the fundamental geometrical and physical characteristics of turbulence fluctuations related with stress components, it is more reasonable to observe the modulations on the invariants than those of any individuals.…”
Section: Modulations Of the Tensor Invariants Of The Reynolds Stress mentioning
confidence: 99%
“…Experimental investigations by means of the particle image velocity (PIV), the laser Doppler anemometry (LDA), the phase Doppler particle analyzer (PDPA) and the high speed camera (HSC) have been measured successfully the hydrodynamics of gas-particle turbulent flows [6][7][8][9][10][11][12][13][14][15][16][17] . As for the LDA technique, Kulick et al 1994 [6] studied the interactions between small-dense Copper and glass beads with diameter of 70 μm, 50 μm and 90 μm and gas turbulence behaviors in fully developed channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 By use of the PIV instrument, the presence of particles noticeably alters the carrier phase turbulence properties through an effective increase in the wall friction velocity of approximately 7% and an increase in normal and shear Reynolds stress by approximately 8–10% in the outer flow. 10 Particle inertia are of great importance for gas turbulence modification, even if the lower mass loading ratio of 5 × 10 –4 . It was attenuated with increasing particle size and mass loadings.…”
Section: Introductionmentioning
confidence: 99%